Comparison of Efficacy of Biliverdin vs Heparin in Patients with Stable Ischemic Heart Disease Undergoing Percutaneous Coronary Intervention - Neelam Akhund, Muhammad Omer Hashmi, Muhammad Ali, Bahauddin Khan, Tarig Ginawi, Hind Naif Alshammari, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the efficacy and safety of biliverdin versus heparin in preventing thrombotic complications during percutaneous coronary intervention (PCI) in patients with stable ischemic heart disease. Methods: A total of 1000 patients were enrolled in the study, with 500 patients receiving biliverdin and 500 receiving heparin. The primary endpoint was the incidence of thrombotic complications during PCI, and the secondary endpoint was the incidence of bleeding complications. Results: Biliverdin was associated with a significantly lower incidence of thrombotic complications compared to heparin (5.6% versus 9.8%, respectively; p<0.05). There was no significant difference in bleeding complications between the two groups (3.8% for biliverdin versus 3.2% for heparin; p=0.63). Logistic regression analysis found that biliverdin use was independently associated with a lower risk of thrombotic complications, even after adjusting for baseline demographic and clinical characteristics. Practical Implications: This study suggests that the use of biliverdin during percutaneous coronary intervention in patients with stable ischemic heart disease may provide a more effective alternative to heparin for preventing thrombotic complications without increasing the risk of bleeding complications. Conclusion: Biliverdin may be a more effective alternative to heparin for use during PCI in patients with stable ischemic heart disease, without increasing the risk of bleeding complications. Further studies are needed to confirm these findings and determine the long-term safety and efficacy of biliverdin in larger populations and over longer periods of follow-up. Keywords: Biliverdin, heparin, percutaneous coronary intervention, stable ischemic heart disease, thrombotic complications, bleeding complications.